Wear reduction mechanisms in modulated turning of compacted graphite iron with coated carbide tool. (February 2023) - Sandoval, Juan; Ali, Aaqib; Kwon, Patrick; Stephenson, David; Guo, Yang
Abstract: Tool wear evolution is characterized in detail for turning compacted graphite iron (CGI) with coated carbide tool under conventional machining (CM) and modulation-assisted machining (MAM) in dry and lubricated conditions at a speed of 250 m/min. Significant wear reductions are achieved by MAM compared to CM turning. MAM dry turning leads to lower tool wear than MAM lubricated turning. It is found that two wear phenomena account for the wear reduction in MAM: 1) the formation of SiO2 deposition layer on tool flank and 2) the preservation of the coatings on the cutting edge. The mechanisms on how the wear progression is slowed down by the observed wear phenomena as well as these phenomena are enabled by MAM are discussed.